Disturbances of Shared Intentionality in Schizophrenia and Autism - Salice, Alessandro; Henriksen, Mads Gram (Frontiers in Psychiatry, 2021)
Schizophrenia and autism are today considered complex spectrum disorders characterised by difficulties in social behaviour. Drawing on recent advances in collective or shared intentionality studies, we present a novel theoretical approach to these social difficulties by exploring them from the angle of shared intentionality. We begin by describing two forms of shared intentionality: joint intentionality and we-intentionality. Joint intentionality crucially relies on the agents’ mentalising abilities such as mindreading and the ability to factor in (or ‘to be moved’ by) their partner’s intentions in deliberation and action planning. By contrast, we-intentionality relies on the agents’ capacity to understand themselves as group members and to adopt the group’s perspective. In schizophrenia spectrum disorders, we propose that joint intentionality remains unaffected, but we-intentionality may be impaired. In severe autism spectrum disorder (i.e. infantile autism), we propose that both forms of shared intentionality are impaired. We suggest that the source of the problems affecting we-intentionality in schizophrenia spectrum disorders lies primarily in trait-like, anomalous self-experiences. In severe autism spectrum disorder, we suggest that problems with mindreading, the ability to ‘be moved’ by others’ intentions, and with the capacity for perspective-taking impede both forms of shared intentionality.